The therapeutic effects of MSc1 nanocomplex, synthesized by nanochelating technology, on experimental autoimmune encephalomyelitic C57/BL6 mice - Fakharzadeh S (Dove Medical Press, 2014)
Saideh Fakharzadeh,1 Mohammad Ali Sahraian,2 Maryam Hafizi,1 Somayeh Kalanaky,1 Zahra Masoumi,1 Mehdi Mahdavi,1 Nasser Kamalian,3 Alireza Minagar,4 Mohammad Hassan Nazaran1 1Department of Research and Development, Sodour Ahrar Shargh Company, Tehran, Iran; 2MS Research Center, Neuroscience Institute, Tehran University of Medical Sciences, Tehran, Iran; 3Department of Pathology, Medical School of Tehran University of Medical Sciences, Tehran, Iran; 4Department of Neurology, LSU Health Sciences Centre, Shreveport, LA, USA Purpose: Currently approved therapies for multiple sclerosis (MS) at best only slow down its progression. Therefore, it is necessary to utilize novel technologies in order to synthesize smart multifunctional structures. In the present study, for the first time we evaluated the therapeutic potential of MSc1 nanocomplex, which was designed based on novel nanochelating technology. Materials and methods: MSc1 cell-protection capacity, with and without iron bond, was evaluated against hydrogen peroxide (H2O2)-induced oxidative stress in cultured rat pheochromocytoma-12 cells. The ability of MSc1 to maintain iron bond at pH ranges of 1–7 was evaluated. Nanocomplex toxicity was examined by estimating the intraperitoneal median lethal dose (LD50). Experimental autoimmune encephalomyelitic mice were injected with MSc1 14 days after disease induction, when the clinical symptoms appeared. The clinical score, body weight, and disease-induced mortality were monitored until day 54. In the end, after collecting blood samples for assessing hemoglobin and red blood cell count, the brains and livers of the mice were isolated for hematoxylin and eosin staining and analysis of iron content, respectively. Results: The results showed that MSc1 prevented H2O2-induced cell death even after binding with iron, and it preserved its bond with iron constant at pH ranges 1–7. The nanocomplex intraperitoneal LD50 was 1,776.59 mg/kg. MSc1 prompted therapeutic behavior and improved the disabling features of experimental autoimmune encephalomyelitis, which was confirmed by decreased clinical scores versus increased body mass and 100% survival probability. It did not cause any adverse effects on hemoglobin or red blood cell count. Histopathological studies showed no neural loss or lymphocyte infiltration in MSc1-treated mice, while the hepatic iron content was also normal. Conclusion: These results demonstrate that MSc1 could be a promising beneficial novel agent and has the capacity to be evaluated in further studies. Keywords: EAE, multiple sclerosis, MSc1, nanochelating technology, nanocomplex